Landscape of RNA-binding proteins in diagnostic utility, immune cell infiltration and PANoptosis features of heart failure - Li, Jie; Zhang, Xueqin; Ren, Peng; Wu, Yu; Wang, Yaoguo; Zhou, Wenzheng; Wang, Zhao; Chao, Peng (Frontiers in Genetics, 2022)
Objective: Heart failure remains a global public health problem linked to rising morbidity and mortality. RNA-binding proteins (RBPs) are crucial regulators in post-transcriptionally determining gene expression. Our study aimed to comprehensively elucidate the diagnostic utility and biological roles of RBPs in heart failure. Methods: Genomic data of human failing and nonfailing left ventricular myocardium specimens were retrieved from the GEO datasets. Heart failure-specific RBPs were screened with differential expression analyses, and RBP-based subtypes were clustered with consensus clustering approach. GSEA was implemented for comparing KEGG pathways across subtypes. RBP-based subtype-related genes were screened with WGCNA. Afterwards, characteristic genes were selected through integrating LASSO and SVM-RFE approaches. A nomogram based on characteristic genes was established and verified through calibration curve, decision curve and clinical impact curve analyses. The abundance of immune cell types was estimated with CIBERSORT approach. Results: Heart failure-specific RBPs were determined, which were remarkably linked to RNA metabolism process. Three RBP-based subtypes (namely C1, C2, C3) were established, characterized by distinct pathway activities and PANoptosis gene levels. C2 subtype presented the highest abundance of immune cells, followed by C1 and C3. Afterwards, ten characteristic genes were selected, which enabled to reliably diagnose heart failure risk. The characteristic gene-based nomogram enabled to accurately predict risk of heart failure, with the excellent clinical utility. Additionally, characteristic genes correlated to immune cell infiltration and PANoptosis genes. Conclusion: Our findings comprehensively described the roles of RBPs in heart failure. Further research is required for verifying the effectiveness of RBP-based subtypes and characteristic genes in heart failure.